2019
DOI: 10.3390/ijms20184606
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Curcumin on the Cytochrome P450 Enzymes of the Steroidogenic Pathway

Abstract: Turmeric, a popular ingredient in the cuisine of many Asian countries, comes from the roots of the Curcuma longa and is known for its use in Chinese and Ayurvedic medicine. Turmeric is rich in curcuminoids, including curcumin, demethoxycurcumin, and bisdemethoxycurcumin. Curcuminoids have potent wound healing, anti-inflammatory, and anti-carcinogenic activities. While curcuminoids have been studied for many years, not much is known about their effects on steroid metabolism. Since many anti-cancer drugs target … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 98 publications
0
19
0
Order By: Relevance
“…This observation is likely attributed to the downregulation of the activity of cytochrome P450c17. Curcumin has been demonstrated to reduce the activity of cytochrome P450c17 in a dose-dependent manner in vitro [ 63 ]. In an animal model, the expression of cytochrome P450c17 in the ovaries of the curcumin-treated mice is reduced to the same level as in those of the wild-type ones [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is likely attributed to the downregulation of the activity of cytochrome P450c17. Curcumin has been demonstrated to reduce the activity of cytochrome P450c17 in a dose-dependent manner in vitro [ 63 ]. In an animal model, the expression of cytochrome P450c17 in the ovaries of the curcumin-treated mice is reduced to the same level as in those of the wild-type ones [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that curcumin could bind to the active sites of steroid metabolizing P450s and the inhibition of CYP17A1 and CYP19A1 provides a template for structural modifications to produce effective and safe compounds to inhibit the growth of prostate cancer as well as breast cancer. 49 However, there are still lack of studies on curcumin evaluating the inhibitory effects on cytochrome P450 and thus as an anti-lung cancer agent, which provides a direction for future research. Curcumin has been reported to inhibit the invasion and metastasis of many cancer cells, including lung cancer, by upregulating the expression of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…Activities of CYP17A1 and CYP19A1 were measured with WT or the P228L variant of POR using methods described in detail in our previous publications [ 14 , 18 , 20 , 21 , 30 , 40 , 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%